Distinct roles of the meningeal layers in CNS autoimmunity - Merlini, Arianna; Haberl, Michael; Strauss, Judith; Hildebrand, Luisa; Genc, Nafiye; Franz, Jonas; Chilov, Dmitri; Alitalo, Kari; Flügel-Koch, Cassandra; Stadelmann, Christine; Fluegel, Alexander; Odoardi, Francesca (Nature Neuroscience, 2022)
The meninges, comprising the leptomeninges (pia and arachnoid layers) and the pachymeninx (dura layer), participate in central nervous system (CNS) autoimmunity, but their relative contributions remain unclear. Here we report on findings in animal models of CNS autoimmunity and in patients with multiple sclerosis, where, in acute and chronic disease, the leptomeninges were highly inflamed and showed structural changes, while the dura mater was only marginally affected. Although dural vessels were leakier than leptomeningeal vessels, effector T cells adhered more weakly to the dural endothelium. Furthermore, local antigen-presenting cells presented myelin and neuronal autoantigens less efficiently, and the activation of autoreactive T cells was lower in dural than leptomeningeal layers, preventing local inflammatory processes. Direct antigen application was required to evoke a local inflammatory response in the dura. Together, our data demonstrate an uneven involvement of the meningeal layers in CNS autoimmunity, in which effector T cell trafficking and activation are functionally confined to the leptomeninges, while the dura remains largely excluded from CNS autoimmune processes.
CRIS-Team Scopus Importer:2022-07-08